2015
DOI: 10.1111/tid.12358
|View full text |Cite
|
Sign up to set email alerts
|

Infectious complications following allogeneic stem cell transplantation by using anti‐thymocyte globulin‐based myeloablative conditioning regimens in children with hemoglobinopathies

Abstract: The rate of infections after allo-SCT, using an ATG-containing preparative regimen, in our population of pediatric patients with hemoglobinopathies is comparable to that reported elsewhere with the use of non-ATG containing regimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 27 publications
4
8
0
Order By: Relevance
“…These infectious complications are similar to those in patients transplanted without in vivo T cell depletion (32). However, rates of GVHD were lower after ATG-based conditioning (32).…”
Section: Disease-specific Outcomes Hemoglobinopathiessupporting
confidence: 63%
See 3 more Smart Citations
“…These infectious complications are similar to those in patients transplanted without in vivo T cell depletion (32). However, rates of GVHD were lower after ATG-based conditioning (32).…”
Section: Disease-specific Outcomes Hemoglobinopathiessupporting
confidence: 63%
“…In order to prevent graft failure/rejection, in vivo T cell depletion is increasingly utilized in patients with hemoglobinopathies (32). An evaluation of IR in children with severe β thalassemia major following matched sibling donor (MSD) HCT found that the addition of ATG led to delayed CD8 T cell recovery at 6 months but no change in CD4 T cell reconstitution, which occurred at 12 months (33).…”
Section: Disease-specific Outcomes Hemoglobinopathiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, the use of myeloablative ATG-containing regimen is associated with a high risk of infections, including CMV, EBV, bacteremia, and invasive fungal infections. 10 In our material, we observed a relatively high incidence of bacterial infections and EBV viremia.…”
Section: Discussionmentioning
confidence: 55%